2018
DOI: 10.1039/c7dt03823b
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of the laser borane anti-B18H22 with pyridine: a structural and photophysical study of some unusually structured macropolyhedral boron hydrides

Abstract: Reaction of anti-BH1 with pyridine in neutral solvents gives sparingly soluble BH-3',8'-Py3a as the major product (ca. 53%) and BH-6',9'-Py2 (ca. 15%) as the minor product, with small quantities of BH-8'-Py 4 (ca. 1%) also being formed. The three new compounds 2, 3a and 4 are characterized by single-crystal X-ray diffraction analyses and by multinuclear multiple-resonance NMR spectroscopy. Compound 2 is of ten-vertex nido:ten-vertex arachno two-atoms-in-common architecture, long postulated for a species with b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 71 publications
1
30
0
Order By: Relevance
“…[65] Similar to our results, the around 1.5 cm À 1 SOC values between S 1 state and T 1 state were obtained as evidence for the low but non-negligible ISC probability, allowing triplet state population and weak phosphorescence in pyridine(Py)-substituted boron cluster B 16 H 18 Py 2 . [29] Quantum dynamics simulations showed that ultrafast ISC occurs in small aromatic hydrocarbons such as benzene via spin-vibronic effects activated by the prefulvene mode where weakly coupled states (S 1 , T 2 , T 1 states) are near degenerate, leading to efficient crossing. [66][67][68][69] We anticipate that quantum dynamics simulations will provide more insights into the photochemical and photophysical processes of B(ppy)Mes 2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[65] Similar to our results, the around 1.5 cm À 1 SOC values between S 1 state and T 1 state were obtained as evidence for the low but non-negligible ISC probability, allowing triplet state population and weak phosphorescence in pyridine(Py)-substituted boron cluster B 16 H 18 Py 2 . [29] Quantum dynamics simulations showed that ultrafast ISC occurs in small aromatic hydrocarbons such as benzene via spin-vibronic effects activated by the prefulvene mode where weakly coupled states (S 1 , T 2 , T 1 states) are near degenerate, leading to efficient crossing. [66][67][68][69] We anticipate that quantum dynamics simulations will provide more insights into the photochemical and photophysical processes of B(ppy)Mes 2.…”
Section: Discussionmentioning
confidence: 99%
“…CIs are crossings between the potential energy surfaces of the same multiplicity, which act as efficient decay funnels from excited states to ground state . CIs have proven to play crucial roles in boron cluster chemistry and to be basic mechanistic elements for important photophysical and photochemical processes such as intramolecular electron transfer, photoisomerization, Wolff rearrangement, Curtius rearrangement, and aggregation‐induced emission …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even if, and especially in the case of ultrafast processes and high excess of kinetic energy, other areas of higher energy can be visited, and only dynamic methods would allow to estimate their relevance, MEPs represent the most probable evolution of a chemical system. Indeed, the calculations of MEPs connecting Franck‐Condon regions with excited‐state minima and conical intersections in the framework of the Photoreactive Path Approach (PRPA) has allowed significant breakthrough in the study of photochemical and photophysical processes of organic and inorganic systems . As pointed out by Lindh and co‐workers, “ PRPA is based on mapping the path for the most efficient energy relaxation in the excited state […] Only this procedure guarantees accurate results within the static model” .…”
Section: Potential Energy Surfacesmentioning
confidence: 99%
“…This invention set a key milestone in the field of lasers. Since then, -B 18 H 22 has aroused deep interest of relevant scientists and witnessed increasingly relevant reports [16][17][18].…”
Section: Introductionmentioning
confidence: 99%